Aqueous ExtractofAdenia cissampeloidesModulates Pain in Mice - O A Adebiyi, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Aqueous ExtractofAdenia cissampeloidesModulates Pain in Mice